VISUAL LITERACY IN THE GRAPHIC NOVEL “NESTE GANG BLIR ALT RIKTIG (EVERYTHING WILL BE ALL RIGHT NEXT TIME)” BY LENE ASK - Raluca‐Daniela RĂDUȚ (Studia Universitatis Babeş-Bolyai. Philologia, 2020)
Visual Literacy in the Graphic Novel Neste Gang Blir Alt Riktig (Everything Will Be All Right Next Time) by Lene Ask. This article aims at analysing the novel Neste Gang Blir Alt Riktig (Everything Will Be All Right, Next Time) written by the Norwegian writer and illustrator Lene Ask (b. 1962) by using the close reading technique and the concept of visual literacy which emphasises the importance of the pictures in the understanding and the interpretation of this graphic novel. With respect to the interpretative level of the book, the accent is placed on the analysis and the evolution of the main character, Marit, and the effect of her dysfunctional family and her parents’ behaviour on her development as a grown-up. Marit’s simple and yet complicated life is presented from two main perspectives, a narrative and a visual one, aiming both her past and present.